First Let we solve the Original system of equations:
equation (1): ![x+3y=5](https://tex.z-dn.net/?f=%20%20x%2B3y%3D5%20)
equation (2): ![7x-8y=6](https://tex.z-dn.net/?f=%207x-8y%3D6%20)
Multiplying equation (1) by 7, we get
![7x+21y=35 -->(3)](https://tex.z-dn.net/?f=%20%207x%2B21y%3D35%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20--%3E%283%29%20)
![7x-8y=6 --> (2)](https://tex.z-dn.net/?f=%20%20%20%20%207x-8y%3D6%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20--%3E%20%282%29%20)
Subtracting,
implies ![y=1](https://tex.z-dn.net/?f=%20y%3D1%20)
Then
Thus the solution of the original equation is![x=2, y=1.](https://tex.z-dn.net/?f=%20%20x%3D2%2C%20y%3D1.%20)
Now Let we form the new equation:
Equation 2 is kept unchanged:
Equation (2):![7x-8y=6](https://tex.z-dn.net/?f=%20%207x-8y%3D6%20)
Equation 1 is replaced with the sum of equation 1 and a multiple of equation 2:
Equation (1): ![8x-5y=11](https://tex.z-dn.net/?f=%208x-5y%3D11%20)
Now solve this two equations: ![8x-5y=11, \\ 7x-8y=6](https://tex.z-dn.net/?f=%208x-5y%3D11%2C%20%5C%5C%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%207x-8y%3D6%20)
Multiply (1) by 7 and (2) by 8,
![56x-35y=77](https://tex.z-dn.net/?f=%20%2056x-35y%3D77%20)
![56x-64y=48](https://tex.z-dn.net/?f=%20%20%2056x-64y%3D48%20)
Subtracting,
implies ![y=1](https://tex.z-dn.net/?f=%20y%3D1%20)
Then x=2.
so the solution for the new system of equation is x=2, y=1.
This Show that the solution to the system of equations 8x − 5y = 11 and 7x − 8y = 6 is the same as the solution to the given system of equations
Answer: OC
Step-by-step explanation: exact answer is 64.6
Answer:
<h2>
150</h2>
Step-by-step explanation:
Given,
u = 2
t = 3
Now, Finding the value of s
![s = ut \: + 16 {t}^{2}](https://tex.z-dn.net/?f=s%20%3D%20ut%20%5C%3A%20%20%2B%2016%20%7Bt%7D%5E%7B2%7D%20)
Plugging the values of u and t
![s = 2 \times 3 + 16 \times {( 3)}^{2}](https://tex.z-dn.net/?f=s%20%3D%202%20%5Ctimes%203%20%2B%2016%20%5Ctimes%20%20%7B%28%203%29%7D%5E%7B2%7D%20)
Calculate
![s = 2 \times 3 + 16 \times 9](https://tex.z-dn.net/?f=s%20%3D%202%20%5Ctimes%203%20%2B%2016%20%5Ctimes%209)
![s = 6 + 144](https://tex.z-dn.net/?f=s%20%3D%206%20%2B%20144)
Calculate the sum
![s = 150](https://tex.z-dn.net/?f=s%20%3D%20150)
Hope this helps ..
Good luck on your assignment..
Answer:
i dont know
Step-by-step explanation:
Erm
x+y=6
xy=12
x+y=6
y=6-x
sub back
xy=12
x(6-x)=12
6x-x^2=12
x^2-6x=-12
x^2-6x+12=0
quadratic formula
for
ax²+bx+c=0
![x= \frac{-b+/- \sqrt{b^2-4ac} }{2a}](https://tex.z-dn.net/?f=x%3D%20%5Cfrac%7B-b%2B%2F-%20%5Csqrt%7Bb%5E2-4ac%7D%20%7D%7B2a%7D%20)
for
x²-6x+12=0
a=1
b=-6
c=12
and remember that √-1=i
![x= \frac{-(-6)+/- \sqrt{(-6)^2-4(1)(12)} }{2(1)}](https://tex.z-dn.net/?f=x%3D%20%5Cfrac%7B-%28-6%29%2B%2F-%20%5Csqrt%7B%28-6%29%5E2-4%281%29%2812%29%7D%20%7D%7B2%281%29%7D%20)
![x= \frac{6+/- \sqrt{36-48} }{2}](https://tex.z-dn.net/?f=x%3D%20%5Cfrac%7B6%2B%2F-%20%5Csqrt%7B36-48%7D%20%7D%7B2%7D%20)
![x= \frac{6+/- \sqrt{-12} }{2}](https://tex.z-dn.net/?f=x%3D%20%5Cfrac%7B6%2B%2F-%20%5Csqrt%7B-12%7D%20%7D%7B2%7D%20)
![x= \frac{6+/- (\sqrt{-1})(\sqrt{12}) }{2}](https://tex.z-dn.net/?f=x%3D%20%5Cfrac%7B6%2B%2F-%20%28%5Csqrt%7B-1%7D%29%28%5Csqrt%7B12%7D%29%20%7D%7B2%7D%20)
![x= \frac{6+/- (i)(2\sqrt{3}) }{2}](https://tex.z-dn.net/?f=x%3D%20%5Cfrac%7B6%2B%2F-%20%28i%29%282%5Csqrt%7B3%7D%29%20%7D%7B2%7D%20)
![x= \frac{6+/- 2i\sqrt{3} }{2}](https://tex.z-dn.net/?f=x%3D%20%5Cfrac%7B6%2B%2F-%202i%5Csqrt%7B3%7D%20%7D%7B2%7D%20)
x=3+/-i√3
the numbers are 3+i√3 and 3-i√3
no real numbers tho